Sistem Diagnostik Mata Digital berbasis Optoscope untuk Deteksi Dini Gangguan Penglihatan secara Akurat dan Efisien - Mufti Ari Bianto; Mohammad Huda Adi Sanjaya; Yuni Furoida Maknuna; Adam Rizky Al’insani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The development of digital technology has had a significant impact on the health sector, including eye examination services. This study discusses the development and implementation of a Digital Optoscope-based Eye Diagnostic application designed using a web platform (HTML). This application provides two main features: visual acuity testing and astigmatism testing, which can be accessed independently by users through digital devices such as laptops, tablets, or mobile phones. Users only need to follow the visual instructions presented interactively on the screen, then perform the test according to the procedure. The testing method is carried out by displaying font size settings according to the Snellen chart standard and radial astigmatism patterns. The results of each test session are automatically recorded and can be saved for further analysis. In addition, users can perform repeated tests to improve the accuracy of self-diagnosis, and the system will provide lens type recommendations based on the measurement results obtained. The trial results show that this application is able to provide convenience, efficiency, and initial accuracy in the process of examining vision disorders. This is very useful, especially for people in remote areas or with limited access to professional eye health services. Thus, the Digital Optoscope-based Eye Diagnostic application has the potential to be an innovative solution for the early digital detection of vision disorders. This study recommends further development, particularly in clinical validation, testing on a wider sample size, and integration with electronic medical record systems to enhance its benefits in comprehensive public health services. Furthermore, collaboration with medical professionals is crucial to ensure diagnostic accuracy. With this approach, the app is expected to become a reliable tool for continuous eye health monitoring.